Genetic Heterogeneity of Australian Candida auris Isolates: Insights From a Nonoutbreak Setting Using Whole-Genome Sequencing. (7th May 2020) - Biswas, Chayanika; Wang, Qinning; van Hal, Sebastiaan J; Eyre, David W; Hudson, Bernard; Halliday, Catriona L; Mazsewska, Krystyna; Kizny Gordon, Alice; Lee, Andie; Irinyi, Laszlo; Heath, Christopher H; Chakrabarti, Arunaloke; et al.
Abstract: Whole-genome sequencing clustered Australian Candida auris isolates from sporadic cases within clade III. Case isolates were genomically distinct; however, unexpectedly, those from 1 case comprised 2 groups separated by >60 single nucleotide polymorphisms (SNPs) with no isolate being identical, in contrast to outbreaks where isolates from any 1 individual have differed by <3 SNPs. Multidrug resistance was absent. High within-host genetic heterogeneity should be considered when investigating C. auris infections.